Peningkatan Profesionalisme Guru-Guru SMAN 7 Mataram Melalui Penelitian Tindakan Kelas (PTK) - Nurul Hikmah; Nani Kurniati; Tabita Wahyu Triutami; Ulfa Lu’luilmaknun; Dwi Novitasari (Rengganis Jurnal Pengabdian Masyarakat, 2021)
This community service activity was carried out with the aim of increasing the professionalism of senior high school teachers at SMAN 7 Mataram through Classroom Action Research (CAR). This training activity is intended for teachers at SMAN 7 Mataram. The implementation of activities is presented in a workshop approach through lectures, discussions, questions and answers, and simulations. The presentation includes material on CAR, data analysis in CAR accompanied by several examples of proposal drafts and scientific publications related to CAR. The very high motivation of the participants was seen during the implementation of community service activities, in addition to the very positive response of the participants with an enthusiasm level of 90% seen during the implementation of this community service. The level of teacher satisfaction is very high with this activity and they have high hopes that further activities will be held as assistance for CAR activities in schools and are able to produce scientific papers that are worthy of publication.